2017
DOI: 10.3390/membranes7040060
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Effects of Nanoscale Membrane Curvature on Lipid Mobility

Abstract: Recent advances in nanoengineering and super-resolution microscopy have enabled new capabilities for creating and observing membrane curvature. However, the effects of curvature on single-lipid diffusion have yet to be revealed. The simulations presented here describe the capabilities of varying experimental methods for revealing the effects of nanoscale curvature on single-molecule mobility. Traditionally, lipid mobility is revealed through fluorescence recovery after photobleaching (FRAP), fluorescence corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…Finally, it is feasible that the membrane bending itself affects the local effective lipid viscosity and the free diffusion of lipids and proteins through the membrane buds. This effect was observed when membrane curvature was engineered by draping SLBs over nanoparticles and the lipid diffusion was measured with SPT (25,43) but not when measured with fluorescence recovery after photobleaching (FRAP) (44), as expected (34). In comparing the diffusion coefficient measured by SPT to that measured by FRAP or fluorescence correlation spectroscopy, it is critical to consider the differences in sensitivity to detecting mobile versus immobile diffusers, length-and timescale-dependent processes, and subpopulations of diffusers (33,34).…”
Section: Membrane Budding Slows Ctxb and DII Diffusionmentioning
confidence: 81%
See 3 more Smart Citations
“…Finally, it is feasible that the membrane bending itself affects the local effective lipid viscosity and the free diffusion of lipids and proteins through the membrane buds. This effect was observed when membrane curvature was engineered by draping SLBs over nanoparticles and the lipid diffusion was measured with SPT (25,43) but not when measured with fluorescence recovery after photobleaching (FRAP) (44), as expected (34). In comparing the diffusion coefficient measured by SPT to that measured by FRAP or fluorescence correlation spectroscopy, it is critical to consider the differences in sensitivity to detecting mobile versus immobile diffusers, length-and timescale-dependent processes, and subpopulations of diffusers (33,34).…”
Section: Membrane Budding Slows Ctxb and DII Diffusionmentioning
confidence: 81%
“…This effect was observed when membrane curvature was engineered by draping SLBs over nanoparticles and the lipid diffusion was measured with SPT (25,43) but not when measured with fluorescence recovery after photobleaching (FRAP) (44), as expected (34). In comparing the diffusion coefficient measured by SPT to that measured by FRAP or fluorescence correlation spectroscopy, it is critical to consider the differences in sensitivity to detecting mobile versus immobile diffusers, length-and timescale-dependent processes, and subpopulations of diffusers (33,34). The SPT results presented here are consistent with prior SPT results and, as expected, report a slower diffusion rate than FRAP or fluorescence correlation spectroscopy measurements (43,45).…”
Section: Membrane Budding Slows Ctxb and DII Diffusionmentioning
confidence: 81%
See 2 more Smart Citations
“…Theoretical studies have concluded that membrane curvature per se will slow down the diffusion of membrane proteins since it influences the packing in the two leaflets and hence the interaction between the protein and the lipids ( Gov, 2006 ; Yoshigaki, 2007 ; Kabbani et al, 2017 ). This should also be considered as an explanation for variations in τ D , since close to endless combinations of curvature in the focal volume are possible for the same membrane area.…”
Section: Discussionmentioning
confidence: 99%